Whitewater wishes [large type] - Robles, Katherine (Thorndike Press large print Christian romance series., 2023)
"Bridget plans to spend her summer working as a white water rafting guide and studying for her beautician' s license exam. She isn' t looking for romance, and she isn' t impressed with nerdy nurse Drew when he steps into her raft. She' s looking for a strongman like the father she failed, but she finds it hard to resist Drew' s passion for life. As a hospital nurse, Drew loves helping people to heal, but after one of his younger patients dies, Drew feels the need to seize the day. So, he faces his fear of open water and goes white water rafting. He' s attracted to Bridget, but meeting his dream girl couldn' t have come at a worse time. His best friend is in trouble and Drew must decide how far he' s willing to go to keep his friend' s secret. When injury capsizes Bridget' s career, they' ll need strength beyond their own to keep their love afloat"--